The Gingrich senators - Theriault, Sean M., 1972- (Oxford University Press, 2013)
In this book, noted political scientist Sean Theriault documents how former House members, who learned politics at the knee of Newt Gingrich, have been behind the transformation of the US Senate from the venerated chamber of the 1950s into the partisan battleground that is regularly the scorn of even the senators themselves.